2013
DOI: 10.1097/inf.0b013e318299f75c
|View full text |Cite
|
Sign up to set email alerts
|

Desired Vancomycin Trough Serum Concentration for Treating Invasive Methicillin-resistant Staphylococcal Infections

Abstract: Vancomycin area under the curve/minimal inhibitory concentration (AUC/MIC) >400 best predicts the outcome when treating invasive methicillin-resistant Staphylococcus aureus infection; however, trough serum concentrations are used clinically to assess the appropriateness of dosing. We used pharmacokinetic modeling and simulation to examine the relationship between vancomycin trough values and AUC/MIC in children receiving vancomycin 15 mg/kg every 6 hours and methicillin-resistant Staphylococcus aureus MIC of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
125
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 13 publications
3
125
1
5
Order By: Relevance
“…Increasing those patients' dose to achieve a trough concentration of Ͼ15 mg/liter will needlessly raise the AUC and increase the chance of renal injury. This dissociation between the therapeutic AUC and trough concentrations of Ͻ15 mg/ liter or even Ͻ10 mg/liter has also been demonstrated in children (30,31).…”
Section: Discussionmentioning
confidence: 88%
“…Increasing those patients' dose to achieve a trough concentration of Ͼ15 mg/liter will needlessly raise the AUC and increase the chance of renal injury. This dissociation between the therapeutic AUC and trough concentrations of Ͻ15 mg/ liter or even Ͻ10 mg/liter has also been demonstrated in children (30,31).…”
Section: Discussionmentioning
confidence: 88%
“…Trough concentration alone did not precisely predict vancomycin AUC 0 -24 in an individual neonate, and this limitation of the trough concentration was previously shown in children and adults (10,28). To address the imprecision in predicting vancomycin AUC 0 -24 based on a trough concentration, we instead applied a probabilistic framework in which for a given trough concentration, the proportion of neonates who achieved an AUC 0 -24 of Ͼ400 was examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship in adults between trough and AUC 0 -24 may not extrapolate to infants and children. For example, recent studies in children have shown that vancomycin trough concentrations of 15 to 20 mg/liter are not necessary to achieve an AUC 0 -24 of Ͼ400, and lower trough concentrations are adequate to achieve this target (9,10). Neonates also represent a unique population, due to the impact of maturation and development on pharmacokinetics (11), and the extrapolation of findings in adults or children to neonates is potentially prone to error.…”
mentioning
confidence: 99%
“…For vancomycin, explaining 81% of the variability in clearance among neonates using a combination of body weight, PMA, and serum creatinine concentrations allows for more accurate estimation of the probability of achieving a ratio of the 24‐hour area under the concentration vs. time curve to the minimum inhibitory concentration (AUC 24 /MIC) ≥400, which has been associated with improved clinical and microbiological outcomes in adults with lower respiratory tract infections caused by the methicillin‐resistant bacterium Staphylococcus aureus 36. Additionally, more accurate estimation of vancomycin clearance allows us to develop dosing regimens that are less likely to result in potentially toxic trough concentrations 35, 37. Recently, using an externally validated neonatal vancomycin population PK model that incorporates body weight, PMA, and serum creatinine concentrations, we found that the percentage of neonates predicted to achieve a therapeutic AUC 24 was 100% using the population PK model, as compared with 39–51% for dosing regimens recommended in nomograms published by the British National Formulary (based on NeoFax dosing recommendations) and the American Academy of Pediatrics' Red Book 38, 39, 40.…”
Section: Resultsmentioning
confidence: 99%